Terrestrial conservation Lagerstätten : windows into the evolution of life on land - Fraser, Nicholas C.; Sues, Hans-Dieter, 1956- (Dunedin Academic Press Ltd, 2017)
A collection of papers reviewing selected conservation Lagerstätten for terrestrial animals and plants throughout the Phanerozoic worldwide. The synthesis details recent progress in documenting the biodiversity of such extraordinary fossil deposits and elucidating the geological conditions for and biogeochemical processes behind their formation.